Evaluation of the vigor characteristics of soybean seeds (Glycine max (l.) merr.) of demas 1 and dega 1 cultivars under submergence stress - Kadapi, Muhamad; Nuraini, Anne; Yusti, Yusti (AGRICOLA, 2025)
The objective of the study was to evaluate the seed vigor of two soybean cultivars under submergence stress conditions. This research was carried out from January to March 2024 at the Seed Technology Laboratory, Faculty of Agriculture, Universitas Padjadjaran. The first test to compare the two cultivars used the F test as variance analysis, and the differences between the two conditions of water level were measured using the t-test at the 5% significant level. In each treatment, it was replicated 4 times and duplicated. Furthermore, the vigor characters were measured using a plastic rolled paper test (PRP) test for 40 seeds in each test. The results of this study indicate that submergence stress conditions can give a real affection to germination percentage, vigor index, root length, hypocotyl, and epicotyl length. The higher germination percentage and vigor index in submergence stress were obtained in the Demas 1 cultivar, 80% and 7,22 respectively. Besides, the hypocotyl and epicotyl length in submergence stress showed higher compare to Dega 1, 11.58 cm and 2.54 cm, respectively. Even though, the Dega 1 cultivar showed the best response in root length under submergence stress conditions with a length of 6 cm. These results indicated that the different response cultivars on Submergence stress may be caused by the genetic and internal condition of the seed.